Becoming activists: how young athletes use visual tools for civic action and meaning-making within participatory research - Daniel Vieira; Daniel Vieira; Teresa Silva Dias; Teresa Silva Dias; Marta Sampaio; Marta Sampaio; Sofia Castanheira Pais; Sofia Castanheira Pais; Norberto Ribeiro; Norberto Ribeiro; Cosmin Nada; Cosmin Nada; et al. (Frontiers in Political Science)
How can participatory research, combined with visual methods, enable young people to grow as engaged citizens in their communities? This article introduces an innovative methodological design that draws on a Youth Participatory Action Research (YPAR) approach with 33 young athletes aged 11 to 16 from two different educational settings. Based on both observation notes from the community profiling process and visual materials produced by the young people throughout that process, we analyze how they become activists, taking sports as the ground for mobilization and intervention in their communities. Specifically, we examine the visual activist strategies and the visual meaning-making representations that resulted from young people’s engagement in participatory research. Novel findings include the realization that young people with no previous experience in activism strongly prefer visual and performative formats of participation, often in connection with digital and online arenas. Additionally, data analyses reveal that participants particularly value collective moments of learning, negotiation, and preparation of activist actions. This article highlights the increasing prevalence of visual-oriented modes of civic engagement and the potential of participatory methodologies in fostering critical awareness, meaningful decision-making, and a sense of agency among young people.